2001
DOI: 10.1097/00042192-200109000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Postmenopausal hormonal support: discontinuation of raloxifene versus estrogen

Abstract: We conclude that discontinuation of estrogen by women well beyond the age of menopause is high; more than two-thirds discontinue within 2 years of starting. Women starting therapy with raloxifene are 25% percent less likely to discontinue their medication than those starting estrogen, providing some promise that long-term benefits of raloxifene may be more easily achieved than those of estrogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…However, there is evidence that, generally, continuance with HRT may be poor, because of both fears over its long-term effects and the impact of side-effects on quality of life. A retrospective study 101 found that only 28% of members of a large health maintenance organisation (the Kaiser Foundation Health Plan) who had been prescribed oestrogens, for whatever reason, remained on treatment at 24 months. A Spanish RCT 102 in women who had requested HRT following surgical menopause caused by hysterectomy and bilateral oophorectomy for benign disease randomised them to either continuous oestrogen or transdermal oestradiol.…”
Section: Oestrogen: Continuance and Compliancementioning
confidence: 99%
See 1 more Smart Citation
“…However, there is evidence that, generally, continuance with HRT may be poor, because of both fears over its long-term effects and the impact of side-effects on quality of life. A retrospective study 101 found that only 28% of members of a large health maintenance organisation (the Kaiser Foundation Health Plan) who had been prescribed oestrogens, for whatever reason, remained on treatment at 24 months. A Spanish RCT 102 in women who had requested HRT following surgical menopause caused by hysterectomy and bilateral oophorectomy for benign disease randomised them to either continuous oestrogen or transdermal oestradiol.…”
Section: Oestrogen: Continuance and Compliancementioning
confidence: 99%
“…88,99 Although the relationship between BMD and fracture risk is well established in untreated cohorts, the relationship between a change in BMD and change in fracture risk is less secure. 97,100,101 Indeed, recent RCT data indicate that treatment-induced changes in BMD may underestimate anti-fracture efficacy, i.e. the decrease in fracture rate is greater than that which can be explained on the basis of the measurement of BMD alone.…”
mentioning
confidence: 99%
“…Several studies reported that up to 50% of postmenopausal women were not adherent to their treatment after one to 5 years of HRT (114)(115)(116)(117)(118). A major cause of non-compliance were unwanted side-effects or fear of side-effects, inconvenience caused by medication, and high drug costs (119,120).…”
Section: Monitoring Patient Compliance Using Bone Markersmentioning
confidence: 99%
“…Compared to the base-case, the cost per event avoided increases by 30% if raloxifene does not reduce CHD risk but decreases by 23% if the magnitude of the risk reduction is as large as 35% (similar to the point estimate for the high-risk subgroup in MORE). Improved persistence, as suggested by the results of the Kayser, Ettinger, and Pressman study, 26 would improve cost-effectiveness, but not dramatically so. The population targeted for intervention also has some impact-among women at 2 times the normal agerelated risk for breast cancer, the cost per event avoided falls to $266,000 over 7 years.…”
Section: Dollars (1000s)/event Avoidedmentioning
confidence: 93%
“…However, a recent analysis of data from a large managed care organization found that discontinuation rates at one year after initiation were higher for estrogen-progestin therapy compared to raloxifene. 26 The base model assumes that 41% of patients are persistent at the end of the first year and 26%, 19%, 17%, 15%, 14%, and 13% are persistent at the end of the second through seventh year, respectively. Alternative scenarios are used to evaluate the impact of discontinuation rate assumptions.…”
Section: Therapy Persistence Ratesmentioning
confidence: 99%